Angular acceleration compensation guidance law for passive homing missiles - Li Jixin; Liang Xiaogeng; Xia Keqiang; You Yilin (Open Astronomy, 2022)
Proportional navigation guidance law (PNG) is widely used for passive homing missiles. But PNG often suffers from inaccurate tracking of target or even failure when the target is maneuvering quickly or releasing artificial decoys. In order to solve this problem, the angular acceleration compensation guidance law (AACG) is constructed by using line of sight (LOS) angular velocity and LOS angular acceleration. The stability analysis with Lyapunov stability theory shows that AACG system is asymptotically stable on a large scale under certain stability constraint conditions. AACG command is designed to be perpendicular to the LOS and optimized by gravity compensation. AACG is neither dependent on target acceleration nor the distance between the missile and the target. The numerical simulation results indicate that AACG has good guidance performance on air-to-air missiles when the target maneuvers violently or releases artificial decoys in the endgame term.